Intrinsic protein disorder could be overlooked in cocrystallization conditions: An SRCD case study. (23rd August 2016) - Németh, Eszter; Balogh, Ria K.; Borsos, Katalin; Czene, Anikó; Thulstrup, Peter W.; Gyurcsik, Béla
Abstract: X‐ray diffractometry dominates protein studies, as it can provide 3D structures of these diverse macromolecules or their molecular complexes with interacting partners: substrates, inhibitors, and/or cofactors. Here, we show that under cocrystallization conditions the results could reflect induced protein folds instead of the (partially) disordered original structures. The analysis of synchrotron radiation circular dichroism spectra revealed that the Im7 immunity protein stabilizes the native‐like solution structure of unfolded NColE7 nuclease mutants via complex formation. This is consistent with the fact that among the several available crystal structures with its inhibitor or substrate, all NColE7 structures are virtually the same. Our results draw attention to the possible structural consequence of protein modifications, which is often hidden by compensational effects of intermolecular interactions. The growing evidence on the importance of protein intrinsic disorder thus, demands more extensive complementary experiments in solution phase with the unligated form of the protein of interest.